Strategisches Nachverhandeln zur Lösung von Anreizproblemen in unvollständigen Verträgen am Beispiel der Wohnungsprivatisierung nach dem Altschuldenhilfegesetz - Birgit Sander (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
Governments may draft contracts with market agents for allocating subsidies and pursuing specific policy goals. Contract enforcement via binding commitments is difficult, however, when exogenous (environmental) and endogenous (behavioural) risks interact. Analyzing the old debt compromise in east German housing, it results that a sophisticated design of contractual incompleteness may provide a reasonable safeguard against opportunistic behaviour. Yet it involves considerable costs and still does not guarantee that policy goals are achieved. The crucial policy question is if contracts can be drafted without creating a one-sided holdup potential or if governments should not co-operate with market agents but commit to policy rules.
Keywords: C71; C78; D82; H54; K12; P20; P30; 330; Wohnungspolitik; Wohnungsbaufinanzierung; Privatisierung; Unvollständiger Vertrag; Transaktionskosten; Anreizvertrag; Verhandlungstheorie; Neue Bundesländer